Foldameric probes for membrane interactions by induced β-sheet folding. Issue 9 (17th December 2015) - Hegedüs, Zsófia; Makra, Ildikó; Imre, Norbert; Hetényi, Anasztázia; Mándity, István M.; Monostori, Éva; Martinek, Tamás A.
Abstract : The adjustment of β-sheet content by β-amino acid substitutions revealed β-sheet folding-dependent biological activity. Abstract : Design strategies were devised for α/β-peptide foldameric analogues of the antiangiogenic anginex with the goal of mimicking the diverse structural features from the unordered conformation to a folded β-sheet in response to membrane interactions. Structure–activity relationships were investigated in the light of different β-sheet folding levels.